(untitled) (Research, Society and Development, 2022)
This article aims to carry out a literature review on carboxytherapy in the treatment of localized fat, in order to clarify and provide another source of research for professionals in the area of aesthetics. Methodology: This is a literature review on the Carboxytherapy technique. Result: Currently there are aesthetic procedures that act effectively in the loss of adiposity, one of them is Carboxytherapy. Conclusion: It is an invasive technique, which uses medicinal carbon dioxide which is injected, with an insulin needle, into the subcutaneous tissue, in order to stimulate the physiological effects to improve circulation and tissue oxygenation. There are not many contraindications, carbon dioxide does not cause adverse effects, systemic described, being, therefore, a safe method, easy to perform.